Towards a transformer transient model as a lumped-distributed parameter system. Issue 3 (2nd May 2017) - Zirka, Sergey E.; Moroz, Yuriy I.; Rahimpour, Ebrahim
Abstract : Purpose: The purpose of this study is to develop a topological model of a three-phase, three-limb transformer for low-frequency transients. The processes in the core limbs and yokes are reproduced individually by means of a dynamic hysteresis model (DHM). A method of accounting for the transformer tank with vertical magnetic shunts at the tank walls is proposed and tested on a 120 MVA power transformer. Design/methodology/approach: The model proposed has been implemented independently in a dedicated Fortran program and in the graphical pre-processor ATPDraw to the ATP version of the electromagnetic transient program. Findings: It was found that the loss prediction in a wide range of terminal voltages can only be achieved using a DHM with variable excess field component. The zero sequence properties of the transformer can be accurately reproduced by a duality-derived model with Cauer circuits representing tank wall sections (belts). Research limitations/implications: In its present form, the model proposed is suitable for low-frequency studies. Its usage in the case when transformer capacitances are involved should be studied additionally. Practical/implications: The presented model can be used either as an independent tool or serve as a reference for subsequent simplifications. Social/implications: The model proposed is aimed at meeting the needs of electrical engineering and ecology-minded customers. Originality/value: Till date, there were no experimental data on zero-sequence behavior of three-phase, three-limb transformer with vertical magnetic shunts, so no verified transient model existed. The model proposed is probably the first that matched this behavior and reproduced measured no-load losses for a wide voltage range.